Regulation of cerebral CYP2D alters tramadol metabolism in the brain: interactions of tramadol with propranolol and nicotine. (12th November 2014) - Wang, Qiaoli; Han, Xiaotong; Li, Jian; Gao, Xinghui; Wang, Yan; Liu, Mingzhou; Dong, Guicheng; Yue, Jiang
Abstract: 1. Cytochrome P450 2D (CYP2D) protein is widely expressed across brain regions in human and rodents. We investigated the interactions between tramadol, a clinically used analgesic, and brain CYP2D regulators, by establishing concentration–time curves of tramadol and O-desmethyltramadol (M1) in rat cerebrospinal fluid (CSF) and plasma, as well as by analyzing the analgesia-time course of tramadol. 2. Propranolol (20 μg, intracerebroventricular injection), CYP2D inhibitor, prolonged the elimination t 1/2 of tramadol (40 mg/kg, intraperitoneal injection) in the CSF; meanwhile, lower C max and AUC0–∞ values of M1 were observed. Nicotine (1 mg base/kg, subcutaneous injection, seven days), brain CYP2D inducer, induced a shorter T max and elevated C max of M1 in CSF. No differences in the peripheral metabolism of tramadol were observed following propranolol and nicotine pretreatment. Nicotine increased areas under the analgesia-time curve (AUC) for 0–45 min and 0–90 min of tramadol, which was attenuated by propranolol administration. The analgesic actions of tramadol positively correlated with cerebral M1 concentration. 3. The results suggest that the regulation of brain CYP2D by xenobiotics may cause drug–drug interactions (DDIs) of tramadol. Brain CYPs may play an important role in DDIs of centrally active substances.